Sequential reactions from catalytic hydroformylation toward the synthesis of amino compounds. Issue 17 (27th April 2017) - Almeida, Ana R.; Carrilho, Rui M.B.; Peixoto, Andreia F.; Abreu, Artur R.; Silva, Artur; Pereira, Mariette M.
Abstract: Different families of new amino compounds were efficiently synthesized, through optimized sequential processes, involving rhodium catalyzed hydroformylation as the key step. The selection of appropriate hydroformylation catalytic systems and reaction conditions allowed obtaining aldehydes derived from several n-alkyl olefins, cholest-4-ene and 3-vinyl-1 H -indole, which were subsequently transformed, in one-pot, in to α-amino acids via hydroformylation/Strecker reaction, and in to tertiary amines via hydroaminomethylation, with excellent yields. Graphical abstract: